Remaking International Trade for a Sustainable Future: Toward an International Trade Organization for the 21st Century - Esty, Daniel (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
This paper argues that the existing trade system needs to be reconfigured to promote sustainable development, economic stability, and international cooperation. It proposes the creation of a new World Trade Organization (WTO) that would build on the successful elements of the Bretton Woods structure but with significant updates to address current global challenges. The new trade system should prioritize sustainable development, incorporating environmental, social, and economic goals. The new trade governance structure should also include a presumption of flexibility for actions taken to address global challenges like climate change. Reciprocity in trade should be determined by a nation's global trade surplus, and the principle of Most Favored Nation treatment should apply only to countries that share common values and adhere to core principles. Overall, the document calls for a reimagined trade system that is more inclusive, sustainable, and aligned with the political and economic realities of the 21st century.